EFFECTIVENESS OF NUTRITIONAL EDUCATION MEDIA FOR STUNTING PREVENTION IN PREGNANT WOMEN - Viviana, Susan; Kurniasari, Ratih (HEARTY, 2024)
Stunting is a health problem related to child’s nutrition where his growth and development process is slower than other children, characterized by the child's height being below compared to the children’s standard his age. This problem is caused by various factors such as nutritional intake and parental knowledge which results in children's nutritional needs not being met during the First 1000 Days of Life. If it is not treated immediately, stunting can reduce a child's immunity and cognitive abilities, making them vulnerable to disease and experiencing difficulties in education. Stunting prevention can be made by educating the public, especially pregnant women, regarding the importance of fulfilling children's nutritional intake with various interesting and innovative media. The aim of this study is to analyze the influence of nutritional education media on stunting prevention in increasing the knowledge of pregnant women. This study was written based on various literature references related to the research title. The results of the research show that there is a significant influence of nutritional education media on stunting prevention in increasing the knowledge of pregnant women. Nutrition education media in stunting prevention plays a role in increasing pregnant women's knowledge about the importance of meeting children's nutritional needs.